Study of Fusion of Sagittal Suture on Computed Tomography Skull with Age in Western Maharashtra - Ashok Narayan; Ishita Manral; Chandni Nair; S.N. Pandam; Sravan Kumar; C.S. Makhani; Hemant Bhardwaj (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: This study examines the relationship between age and sagittal suture closure patterns using both cross-sectional and external measurements. Age is one of the big three of identi𿿿cation. With changing pattern of fusion we wantedtostudy if there is an association between age and suture closure at external and cross-sectional area in skull CT𿿿lms. Methodology: This study examines the closure patterns of sagittal sutures using CT scans analyzed with Radiant DICOM software, correlating them with chronological age and gender. The suture was divided into three pasts-S1, S2 and S3. A total of 100 images were assessed, with intra- and inter-observer reliability ensured through re-evaluations. The study aimed to explore relationships between cross-sectional and external suture closure patterns using statistical analysis. Results: Pearson’s correlations and linear regression were used to identify statistically signi𿿿cant associations. The cross-sectional areas along the sagittal suture exhibit varying degrees of positive correlation with external measurements, with S3 having the strongest correlations. External measurements at S1, S2, S3 orrelated strongly with age, while cross-sectional measurements have weaker positive association. Conclusion: External measurements at S1, S2, S3 correlated strongly with age, while cross-sectional measurements have weaker positive association. S3 has the strongest correlation between external stage and cross-sectional stage.